A Dysmorphic Child with a Pericentric Inversion of Chromosome 8 - Venkateshwari Ananthapur; Srilekha Avvari; Sujatha Madireddi; Pratibha Nallari; Jyothy Akka (Hindawi Limited, 2012)
An 8-year-old boy was referred to our institute with dysmorphic features such as mild lupus, micrognathia, low hair line, hypoplasia, hemi atrophy of left side of the face, abnormal size of ears, hypothenar, hypoplasia of chin, and tongue tie. MRI scan was found to be normal and EEG suggestive of generalized seizure disorder. Cytogenetic evaluation of the proband revealed a pericentric inversion of chromosome 8 with 46, XY, and inv 8 (p11.2; q21.2) karyotype.